Efficacy of Different Combinations of Direct-Acting Antivirals Against Different Hepatitis C Virus-Infected Population Groups: An Experience in Tertiary Care Hospitals in West Bengal, India - Sagnik Bakshi; Partha Chattopadhyay; Mahiuddin Ahammed; Raina Das; Moumita Majumdar; Supradip Dutta; Shreyasi Nath; Anwesha Ghosh; Uttaran Bhattacharjee; Upasana Baskey; Provash Chandra Sadhukhan (Viruses, 2025)
Hepatitis C virus (HCV) is a global public health problem, but advancements in HCV treatment have improved the cure rate. This study evaluated the effectiveness of direct-acting antivirals (DAAs) in HCV-infected patients from May 2021 to April 2023 in collaboration with tertiary care hospitals in West Bengal. The HCV viral load was monitored via qRT-PCR. Sanger sequencing was performed to determine the HCV genotypes. The clinicians prescribed the patient treatment regime. The maximum number of patients in the study population (N = 398) were compensated cirrhosis patients (46.28%). The overall SVR rate of the study population was 94.47%. The decompensated cirrhosis patients experienced the lowest SVR rate (88.89%). The maximum number of patients were prescribed sofosbuvir/daclatasvir (63.77%), and the lowest SVR rate (93.23%) was observed with this treatment regime. In the study population, GT-3 was the predominant (67.43%) circulating genotype, followed by GT-1 and -4. Among 398 patients, 22 (5.53%) were non-responsive to DAA treatment. Out of these 22 non-responder patients, 77.27% (n = 17) were GT-3-infected (3a:10; 3b:07), followed by GT-1 (1c: 04; 1b: 01). Thus, increasing numbers of DAA non-responsive cases among HCV GT-3-infected and decompensated cirrhosis patients may pose serious threats in the future.